Biology and Management of Doveweed (Murdannia nudiflora) in Ornamental Crop Production - Yuvraj Khamare; Chris Marble; Nathan Boyd; Shawn Steed (EDIS)
Doveweed is a common warm-season annual weed in Florida landscapes, container nurseries, and other agricultural production systems. This new 5-page article is written for green industry professionals and others to aid in the identification and management of doveweed in and around ornamental plants. Preemergence and postemergence herbicides are covered, as well as basic information on doveweed biology and growth. Written by Yuvraj Khamare, Chris Marble, Nathan Boyd, and Shawn Steed, and published by the UF/IFAS Environmental Horticulture Department. https://edis.ifas.ufl.edu/ep576